2008
DOI: 10.1029/2008ja013045
|View full text |Cite
|
Sign up to set email alerts
|

Mode trapping in the plasmasphere

Abstract: [1] As a result of its steplike density profile, combined with the monotonically increasing dipole magnetic field close to the Earth, compressional waves propagating outside the plasmapause can tunnel through and be trapped in a narrow layer that acts as a potential well. The spectrum and the spatial structure of these resonant localized modes are discussed for representative plasmasphere parameters. Data from Sub-Auroral Magnetometer Network, British Geological Survey, and International Monitor for Auroral Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…G. Zong et al, 2009), and in the plasmasphere (e.g., X. Shi et al, 2017;Shinbori et al, 2004;Takahashi et al, 2010Takahashi et al, , 2018Takahashi et al, , 2009Turkakin et al, 2008). Knott et al (1985) reported that the dayside magnetospheric electric field shows transient signatures at the onset of SC, and these signatures are followed by oscillations with a period of ∼200 s Fujita et al (2003) used the 3-D MHD simulation to analyze the magnetospheric response to a magnetic impulse and showed that the initial electric field impulse is dominantly dusk-to-dawn direction in the dayside magnetosphere due to the passage of fast compressional mode wave.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…G. Zong et al, 2009), and in the plasmasphere (e.g., X. Shi et al, 2017;Shinbori et al, 2004;Takahashi et al, 2010Takahashi et al, , 2018Takahashi et al, , 2009Turkakin et al, 2008). Knott et al (1985) reported that the dayside magnetospheric electric field shows transient signatures at the onset of SC, and these signatures are followed by oscillations with a period of ∼200 s Fujita et al (2003) used the 3-D MHD simulation to analyze the magnetospheric response to a magnetic impulse and showed that the initial electric field impulse is dominantly dusk-to-dawn direction in the dayside magnetosphere due to the passage of fast compressional mode wave.…”
Section: Resultsmentioning
confidence: 99%
“…Previous observations have demonstrated that the passage of the compressional mode waves can induce the distinct ULF waves in the magnetosphere (e.g., Hudson et al., 2004; Sarris et al., 2010; Q. Shi et al., 2013; Wilken et al., 1982; Q. G. Zong et al., 2009), and in the plasmasphere (e.g., X. Shi et al., 2017; Shinbori et al., 2004; Takahashi et al., 2010, 2018, 2009; Turkakin et al., 2008). Knott et al.…”
Section: Resultsmentioning
confidence: 99%
“…6, 7), which was much smaller than the transverse wave scale of~0.8 R E for the PSW with m-value at a geocentric distance of 4.5 R E , satisfying the requirement of the interface width in exciting surface waves 47 . The sharp discontinuity in the density led the magnetosonic wave to be undamped 24,46,48 , allowing excitation of a standing surface eigenmode, i.e., the PSW propagating sunward/westward at the plasmapause boundary and along the field lines to both the northern and southern polar ionosphere. Using the plasmapause crossing measurements, it is estimated that the frequency of the fundamental poloidal wave is 1.35-2.11 mHz, close to 1.5 mHz (see the Methods section, estimation of eigenfrequency).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that fast mode waves which are generated by SSC/si would propagate through the magnetosphere [ Hudson et al ., ; Sarris et al ., ; Zhang et al ., ; Zong et al ., ]. Furthermore, multipoint observations provide new evidence that fast mode waves can be trapped in the plasmasphere [ Takahashi et al ., , ; Turkakin et al ., ]. Through comparison of magnetic field observations in the topside ionosphere and on the ground, nighttime Pi2 and Pc3 waves at low latitudes are considered to be generated by the direct transmission of fast mode waves toward the ground [ Cuturrufo et al ., ; Pilipenko et al ., ].…”
Section: Introductionmentioning
confidence: 99%